Clinical Outcomes After Isolated Medial Patellofemoral Ligament Reconstruction for Patellar Instability Among Patients With Trochlear Dysplasia. Issue 4 (March 2018) - Liu, Joseph N.; Brady, Jacqueline M.; Kalbian, Irene L.; Strickland, Sabrina M.; Ryan, Claire Berdelle; Nguyen, Joseph T.; Shubin Stein, Beth E.
Background: Medial patellofemoral ligament (MPFL) reconstruction has become one of the most common and widely used procedures to regain stability among patients with recurrent lateral patellar dislocation. While recent studies demonstrated low recurrence rates, improved patient-reported outcome measures, and a high rate of return to sports, limited literature explored its effectiveness as an isolated intervention in the context of trochlear dysplasia. Purpose: To determine the efficacy of isolated MPFL reconstruction in treating patellar instability in the setting of trochlear dysplasia. Study Design: Case series; Level of evidence, 4. Methods: This was a retrospective review of consecutive patients who underwent uni- or bilateral medial patellofemoral ligament reconstruction for patellofemoral instability with a minimum 2-year follow-up. No osteotomies were included. Pre- and postoperative assessment included ligamentous laxity, patellar crepitus, tilt, translation, apprehension, and radiographic features, including tibial tubercle-trochlear groove (TT-TG) distance, Dejour classification, and Caton-Deschamps index. Results: A total of 121 MPFL reconstructions were included. Mean age at surgery was 23.8 years, and 4.4 dislocation events occurred before surgery. Mean follow-up was 44 months; 76% of patients were female. Mean preoperative TT-TG ratio was 13.5, and mean Caton-Deschamps ratio was 1.2; 92% of patients had Dejour B, C, or D trochlear dysplasia. Kujala score improved from 55.0 preoperatively to 90.0 ( P < .001). Almost all patients (94.5%) were able to return to sports at 1 year, with 74% returning to the same or higher level of play. Only 3 patients reported a postoperative dislocation or subluxation event. Discussion: For patients without significantly elevated TT-TG distances or significant patella alta, isolated MPFL reconstruction provides a safe and effective treatment for patellofemoral instability, despite the presence of trochlear dysplasia. Most patients are able to return to sports by 1 year postoperatively at the same or higher level of play.